CroDeriV 2.0: Initial Experiments - Šojat, Krešimir (Array, 2014)
This paper deals with the processing of derivational morphology in Croatian and focuses on the expansion of CroDeriV – a resource with data on morphological structure and derivational relations. The purpose of CroDeriV is to systematically present the morphological structure and derivational relations of Croatian lexemes, and to use this data for the enrichment and development of existing resources and tools, as well as of new ones. One of the objectives in this ongoing project is to build an analyzer for Croatian capable of analyzing both inflectional and derivational morphemes. In this paper we present the initial experiments towards the enlargement of CroDeriV to include nouns, as well as the development of a morphological analyzer for inflectional and derivational morphemes.